2008
DOI: 10.1021/bc800264z
|View full text |Cite
|
Sign up to set email alerts
|

Dark Quenched Matrix Metalloproteinase Fluorogenic Probe for Imaging Osteoarthritis Development in Vivo

Abstract: The early detection of osteoarthritis (OA) is currently a key challenge in the field of rheumatology. Biochemical studies of OA have indicated that matrix metalloproteinase-13 (MMP-13) plays a central role in cartilage degradation. In this study, we describe the potential use of a dark-quenched fluorogenic MMP-13 probe to image MMP-13 in both in vitro and rat models. The imaging technique involved using a MMP-13 peptide substrate, near-infrared (NIR) dye, and a NIR dark quencher. The results from this study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 16 publications
0
79
0
Order By: Relevance
“…Any symptoms associated with OA, such as joint effusion, tenderness, crepitation, decreased range of motion, and alignment of the knee joints, are carefully evaluated by physician. Radiographs typically show joint space narrowing, subchondral sclerosis, marginal osteophytes, and, sometimes, subchondral cyst formation 4. In diagnosis of OA, laboratory tests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Any symptoms associated with OA, such as joint effusion, tenderness, crepitation, decreased range of motion, and alignment of the knee joints, are carefully evaluated by physician. Radiographs typically show joint space narrowing, subchondral sclerosis, marginal osteophytes, and, sometimes, subchondral cyst formation 4. In diagnosis of OA, laboratory tests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other strategies for MMP imaging, which do take full advantage of the nature of the target, are directed at the activity of the enzyme and will provide a selective readout of the activated MMP subpopulation and, importantly, lead to signal amplification because a single MMP can continuously activate its substrate (13). Recently, a variety of substrate-flanked fluorescence resonance energy-transfer probes has been developed to sense MMP activity in living organisms (14)(15)(16)(17)(18). Typically, these smart probes consist of one or multiple intramolecularly quenched fluorophores that become fluorescent on activation.…”
mentioning
confidence: 99%
“…Optical images in various disease models including cancer, atherosclerosis, and myocardial infarction have demonstrated that this probe can image MMP activity in vivo (103105). Lee et al described the potential use of a dark-quenched MMP-13 activatable peptide probe to image overexpressed MMP-13 in an osteoarthritis (OA) model (106) (Fig. 3).…”
Section: Optical Peptide Probesmentioning
confidence: 99%
“…The spectrofluorometry study clearly demonstrated significant recovery (>30-fold) of the NIR fluorescence signals in the samples containing MMP-13, with inhibition of the signal in the presence of a MMP-13 inhibitor. When the probe was injected into an OA-induced rat model, the symptoms of the early and late stages of OA could be simply monitored, imaged, and analyzed (106). …”
Section: Optical Peptide Probesmentioning
confidence: 99%